2017
DOI: 10.1016/j.rmed.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Extrafine compared to non-extrafine particle inhaled corticosteroids in smokers and ex-smokers with asthma

Abstract: Similar effectiveness in improving small airways function was found for extrafine and non-extrafine particle ICS treatment for asthmatic smokers and ex-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“…For this study 77 subjects were screened. However, 18 subjects were excluded as they were unable to perform spirometry or a provocation test adequately ( n = 5), complete the medication washout period ( n = 8), had chronic non-asthmatic respiratory diseases ( n = 2), or had other unstable non-respiratory diseases ( n = 3) [22]. A total of 59 subjects underwent both provocation tests of which 36 performed a MBNW test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study 77 subjects were screened. However, 18 subjects were excluded as they were unable to perform spirometry or a provocation test adequately ( n = 5), complete the medication washout period ( n = 8), had chronic non-asthmatic respiratory diseases ( n = 2), or had other unstable non-respiratory diseases ( n = 3) [22]. A total of 59 subjects underwent both provocation tests of which 36 performed a MBNW test.…”
Section: Resultsmentioning
confidence: 99%
“…This study was performed with baseline data from the previously published OLiVIA study (clinical trial number: NCT01741285, www.clinicaltrials.gov) [22]. Included subjects were asthmatics (doctor’s diagnosis), current or ex-smokers (> 5 pack years), aged between 18 and 65 years, and all had a preserved lung function (FEV 1 > 50%predicted and > 1.2 L).…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that smokers and ex-smokers with asthma would benefit more from extrafine than non-extrafine particle ICS. However, our OLiVIA-study showed that extrafine and non-extrafine particle ICS were equally effective in improving small airways function in current and ex-smokers with asthma [5]. This outcome might be ascribed to the fact that the presence of SAD was not an inclusion criterion in our study.…”
mentioning
confidence: 80%
“…(Clenil) and non-extrafine HFA-fluticasone 250 μg b.i.d. (Flixotide) [5]. The primary outcome was the change in airway hyperresponsiveness (AHR) to small particle adenosine, expressed as the provocative dose of adenosine causing a 20% drop in FEV 1 (forced expiratory volume at 1 s) from baseline to post-treatment (ΔPD 20 ).…”
mentioning
confidence: 99%
“…Data were collected from participants of two asthma studies on ICS treatment: OLiVIA (n = 39, 2‐week HFA‐beclomethasone 200 µg b.i.d . and NZRHS (n = 28, 12‐week budesonide 400 µg b.i.d).…”
mentioning
confidence: 99%